Synthesis, characterization and application of antioxidants nanoparticles incorporated polymeric membranes. Issue 2 (22nd January 2019) - Rajesh, Smitha; Murthy, Z.V.P.
ABSTRACT: Aim of this work is to establish industrial application of antioxidant nanoparticles incorporated polyethersulfone (PES) and polyethyleneterephthalate (PET) membranes. PES and PET blended ultrafiltration (UF) membranes were subjected to surface modification with antioxidant 2, 2ʹ-methylenebis(6-tert-butyl-4-ethylphenol) (MBEP) nanoparticles incorporation, as well as modification with antioxidant 2, 2ʹ-ethylidenebis (4, 6-di-tert-butylphenol) (EBBP) nanoparticles, further, with combination of MBEP/EBBP nanoparticles. Hydrophilicity, stability and anti-fouling of modified membranes were investigated. The modified membranes exhibited much better chemical stability to acid- and alkali solutions, improved the hydrophilicity and water flux. PES/MBEP:EBBP copolymer membranes exhibited excellent fouling tolerance against oily water than normal antioxidant materials.